PENDIDIKAN PEMBEBASAN MENURUT PAULO FREIRE DAN IMPLIKASINYA DALAM PAK MASA KINI DI SMAK LOLI KABUPATEN TIMOR TENGAH SELATAN - Boineno, Misael; Baun, Nofriana; Tiba, Norianti Pai; Rohi, Aldi E. (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The problem in this study is that the learning carried out by Christian Religious Education teachers so far has been more oriented towards increasing knowledge. While in the assessment there are three aspects that need to be done, namely Cognitive, affective and psychomotor or skills. Christian Religious Education teachers need to combine knowledge with various skills needed by the world of work. Therefore, student maturity needs to be equipped with skills that lead to this area. Based on the background of the problem above, the formulation is How is the implementation of Christian Religious Education in schools as a place of liberation for students in facing the challenges of the industrial revolution 4.0 era? The objectives to be achieved in this study are to examine the implementation of Christian Religious Education in schools as a place of liberation for students in facing the challenges of the industrial revolution 4.0 era. The research method used in this study is a descriptive qualitative research method. The subjects in this study are related elements, namely 1 Christian Religious Education Teacher and 20 grade XI students. Data were collected using interview techniques, observation, documentation to obtain accurate data regarding the problems studied. The collected data were processed and analyzed descriptively. Based on the results of the data analysis, it was found that: the implementation of Christian Religious Education at SMAK Loli is based on the contents of the 2013 curriculum. The contents of the Christian Religious Education learning material are adjusted to the contents of the existing curriculum. Christian Religious Education learning activities in class begin with preparation by the Christian Religious Education Subject teacher. The development of learning materials always leads to improving cognitive and affective aspects. While the psychomotor aspect which contains skills is still oriented towards mastering how to pray and lead worship. While the skills needed by students to be able to face the era of the industrial revolution 4.0 have received less attention. Therefore, for the research team, Paulo Freire's thoughts on liberation education have received less attention from Christian Religious Education teachers. Paulo Freire's thoughts need to be implied in contemporary Christian Religious Education so that they prepare students maturely to enter the era of industry 4.0